Are public works programmes effective in reinforcing social protection systems? Evidence from Northern Namibia - Ojijo Odhiambo; Johannes Ashipala; Fabian Mubiana (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
This paper analyses the effectiveness of public works programmes (PWPs) in creating employment, reducing poverty and reinforcing the existing social protection system in Namibia. Using data and information from a survey conducted in northern Namibia, it is established that while public works programmes have no significant effect on the employment status of participants beyond the programme lifespan, they nonetheless have a significant positive effect on their socio-economic well-being. PWP wages, which are significantly lower than those prevailing in the market for unskilled labour, are comparable to most of the existing social cash transfers and have a positive impact on poverty reduction. It is established that PWP wages are used by individuals and households to invest in economic assets as well as in improving access to basic social services - education and health - all of which serve to reinforce the well-developed social protection system. There is, however, a need to constantly review the wage level to be as near the prevailing market rates as possible; to ensure that the PWPs have an inbuilt mechanism for the transfer of the necessary skills; and to design complementary policies and programmes that promote long-term investments in rural areas so that PWPs can be more effective in reinforcing the existing social protection system.
Keywords: 330